2021
DOI: 10.1111/sji.13010
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Inborn errors of immunity in a cohort of 90 patients presenting with complications to BCG vaccination in India

Abstract: World Health Organisation recommends the practice of BCG vaccination at birth in countries which have a high incidence of tuberculosis and/or high leprosy burden. The BCG vaccination is considered safe for a competent immune system. However, in children with weakened immune systems cause of which can be primary or secondary, the vaccine may lead to side effects which can be localized or disseminated. In this study, we report a spectrum of inborn errors of immunity (IEI) commonly referred to as primary immunode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…One example is the Bacille de Calmette et Guérin (BCG) vaccine, which is not routinely administered in many Western countries, but is part of a routine schedule in Japan, where tuberculosis is an endemic disease [2]. This indicates that Japanese IEI patients are at a high risk for BCG-related infections, but although the prevalence of BCG infections has been reported in various countries [3,4], the situation for Japanese IEI patients is unknown. Furthermore, concerns regarding appropriate immunization for IEI patients are increasing, since the number of newly diagnosed IEI patients is expanding due to advances in diagnostic methods such as next generation sequencing (NGS) [5].…”
Section: Introductionmentioning
confidence: 99%
“…One example is the Bacille de Calmette et Guérin (BCG) vaccine, which is not routinely administered in many Western countries, but is part of a routine schedule in Japan, where tuberculosis is an endemic disease [2]. This indicates that Japanese IEI patients are at a high risk for BCG-related infections, but although the prevalence of BCG infections has been reported in various countries [3,4], the situation for Japanese IEI patients is unknown. Furthermore, concerns regarding appropriate immunization for IEI patients are increasing, since the number of newly diagnosed IEI patients is expanding due to advances in diagnostic methods such as next generation sequencing (NGS) [5].…”
Section: Introductionmentioning
confidence: 99%
“…As noted above, he had received the live vaccine BCG (Bacillus Calmette-Guérin). Leucocyte adhesion deficiencies are included in the list of inborn errors of immunity (IEI) that describes complications to the BCG vaccination in India (47). In a retrospective study, inborn errors of immunity were identified in 52 of 90 (58%) individuals who had a localized or disseminated BCG complication; these disorders included LAD1 (47).…”
Section: Discussionmentioning
confidence: 99%
“…Leucocyte adhesion deficiencies are included in the list of inborn errors of immunity (IEI) that describes complications to the BCG vaccination in India (47). In a retrospective study, inborn errors of immunity were identified in 52 of 90 (58%) individuals who had a localized or disseminated BCG complication; these disorders included LAD1 (47). Although he had no evidence of BCG or TB (tuberculosis) disease, these complications (which are generally severe in infants) should be considered, especially in high TB burden countries such as India.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical and pathologic data in this infant confer a predisposition to the weakly virulent mycobacteria, such as that of the BCG vaccine ( 4 ). Thus, this monogenic inherited condition provides an additional insight into the known list of MSMD (Mendelian susceptibility to mycobacterial diseases) ( 1 3 ). This report also advocates for modifying the current practice of early use of BCG ( 8 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since 2005, this vaccine has been administered at birth to all newborns in the United Arab Emirates. Logically, this universal practice is expected to result in a number of "BCG disease, " especially in young infants with inborn error of immunity (IEI) or Mendelian susceptibility to mycobacterial diseases (MSMD) (1)(2)(3). An example of the latter entity is IMD28 (immunodeficiency 28, mycobacteriosis, autosomal recessive; MIM#614889), which results from pathogenic variants of IFNGR2 (interferon-gamma receptor 2; MIM#147569), such as c.123C>G, p.Tyr41 * (4).…”
Section: Introductionmentioning
confidence: 99%